Emergency physicians' experience of stress during resuscitation and strategies for mitigating the effects of stress on performance. Issue 11 (14th December 2021) - Groombridge, Christopher James; Maini, Amit; Ayton, Darshini; Soh, Sze-Ee; Walsham, Nicola; Kim, Yesul; Smit, De Villiers; Fitzgerald, Mark
Abstract : Objective: This study explored the perspectives and behaviours of emergency physicians (EPs), regularly involved in resuscitation, to identify the sources and effects of any stress experienced during a resuscitation as well as the strategies employed to deal with these stressors. Methods: This was a two-centre sequential exploratory mixed-methods study of EPs consisting of a focus group, exploring the human factors related to resuscitation, and an anonymous survey. Between April and June 2020, the online survey was distributed to all EPs working at Australia's largest two major trauma centres, both in Melbourne, and investigated sources of stress during resuscitation, impact of stress on performance, mitigation strategies used, impact of the COVID-19 pandemic on stress and stress management training received. Associations with gender and years of clinical practice were also examined. Results: 7 EPs took part in the focus group and 82 responses to the online survey were received (81% response rate). The most common sources of stress reported were resuscitation of an 'unwell young paediatric patient' (81%, 95% CI 70.6 to 87.6) or 'unwell pregnant patient' (71%, 95% CI 60.1 to 79.5) and 'conflict with a team member' (71%, 95% CI 60.1 to 79.5). The most frequently reported strategies to mitigate stress were 'verbalising a plan to the team' (84%, 95% CI 74.7 to 90.5), 'implementing a standardised/structured approach' (73%, 95% CI 62.7 to 81.6) and 'asking for help' (57%, 95% CI 46.5 to 67.5). 79% (95% CI 69.3 to 86.6) of EPs reported that they would like additional training on stress management. Junior EPs more frequently reported the use of 'mental rehearsal' to mitigate stress during a resuscitation (62% vs 22%; p<0.01) while female EPs reported 'asking for help' as a mitigator of stress more frequently than male EPs (79% vs 47%; p=0.01). Conclusions: Stress is commonly experienced by EPs during resuscitation and can impact decision-making and procedural performance. This study identifies the most common sources of stress during a resuscitation as well as the strategies that EPs use to mitigate the effects of stress on their performance. These findings may contribute to the development of tailored stress management training for critical care clinicians.